PENGARUH LONG TERM DEBT TO EQUITY RATIO DAN SALES GROWTH TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SUB SEKTOR RITEL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2021-2023 - Fatmawati, Ade Pipit; Ramadan, Mohamad Rizky (LAND JOURNAL, 2025)
A retail company is a person or business whose primary business is selling directly to end users in small quantities. After the phenomenon of changes in shopping trends and declining profits that led to the closure of several retail establishments, the author is interested in conducting Conduct research on the subject. This study plans to decide the effect of long haul obligation to value proportion and deals development on monetary trouble in retail subsector organizations recorded between 2021-2023 on the Indonesia Stock Trade. Quantitative techniques and secondary data are used in this investigation. A purposive selection approach was used to pick 105 samples in total. A two-tailed test was used to evaluate the hypothesis. Numerous techniques, including the data normalcy test, coefficient of determination, multiple correlation, product moment correlation, various relapse examination, T test, and F test, were utilized for the information investigation. The review's discoveries show that while long haul obligation to value proportion altogether affects monetary difficulty, deals development affects it.